Persistent Visual Aura following Catheter Ablation in a Patient with WPW Syndrome - Shinichi Koyama; Mitsuru Kawamura (Behavioural Neurology)
We report a patient who has had persistent visual disturbances since she underwent catheter ablation to treat her Wolff-Parkinson-White (WPW) syndrome. We examined her visual symptoms carefully and quantitatively by means of our newly developed method combining image-processing and psychophysics. We first simulated the patient’s visual symptoms using image-processing techniques. Since the simulation indicated that she would be very sensitive to the edges of the visual stimuli, we evaluated her sensitivity to the edges using psychophysics. The results indicated that she was hypersensitive to the clear-cut edges of the visual stimuli. Her visual symptoms were very similar to those of visual aura of migraine, rather than those of photosensitive epilepsy. Magnetic resonance imaging (MRI) and single photon emission computed tomography (SPECT), electroenchepalogram (EEG), and visual-evoked potentials (VEP) in the patient were normal. No abnormalities in her fundus, visual field, or electroretinogram were found, either. Transesophageal echocardiography with bubble study indicated that she had a preexisting right-to-left shunt. We hypothesize that visual aura of migraine was triggered and made persistent by the catheter ablation in this patient. Although the relationship between migraine, catheter ablation, and right-to-left shunts is unknown, previous studies on the transcatheter closure of patent foramen ovale suggest a possible link between them. Catheter ablation in patients with migraine and preexisting shunts may lead to exacerbations in migraine symptoms.